Tax Compliance Behavior, Digital Tax Services, and Business Sustainability: The Role of Perceived Tax Fairness in SME Survival - Siregar, Muhammad Fajeri; Tarigan, Egy Juwita (Manunggal Halim Jaya, 2026)
This study aims to examine the interrelationship between tax compliance behavior, digital tax services, and business sustainability among small and medium-sized enterprises (SMEs), with particular emphasis on the role of perceived tax fairness in supporting SME survival. Using a qualitative research approach based on an in-depth literature study, this research systematically reviews and synthesizes recent and relevant scholarly works on behavioral tax compliance, digital tax administration, and SME sustainability. Academic articles, policy reports, and theoretical studies published in reputable journals were analyzed using thematic analysis to identify dominant patterns, mechanisms, and conceptual linkages among the core constructs. The findings indicate that tax compliance behavior in SMEs is strongly influenced not only by enforcement mechanisms but also by administrative capacity, digital system quality, and institutional trust. Digital tax services contribute positively to compliance and sustainability when they reduce compliance costs, enhance procedural clarity, and are perceived as fair by SME owner-managers. However, when digitalization increases complexity or is perceived as inequitable, it may intensify administrative burdens and weaken business resilience. The study further finds that perceived tax fairness functions as a critical conditioning mechanism that strengthens voluntary compliance and enables SMEs to reallocate resources toward resilience-building activities. Overall, the research highlights that fairness-oriented digital tax administration can simultaneously improve compliance effectiveness and support the long-term sustainability and survival of SMEs, offering important theoretical and managerial implications for sustainable tax policy design.